Environmental and Social Dimensions of Energy Transformation Using Geothermal Energy - Michał Kaczmarczyk; Anna Sowiżdżał (Energies, 2025)
The use of geothermal energy is gaining strategic importance in the context of sustainable development and the decarbonisation of local energy systems. As a stable and low-emission renewable energy source, geothermal energy offers tangible environmental and social benefits, including improved air quality, reduced greenhouse gas emissions, and enhanced energy independence. This article presents a comprehensive overview of the social dimensions of geothermal energy deployment in Poland, with a particular focus on environmental impacts, public acceptance, and participatory governance. Based on a Polish geothermal district heating system example, the paper demonstrates that geothermal projects can significantly reduce local pollution and support low-carbon economic transitions. The study includes a comparative assessment of avoided emissions, a critical discussion of potential social barriers, and SWOT and PESTEL analyses identifying systemic enablers and constraints. The authors argue that for geothermal energy to fulfil its sustainability potential, it must be supported by inclusive planning, transparent communication, and a holistic policy framework integrating environmental, technological, and social criteria.